2022
DOI: 10.1061/(asce)la.1943-4170.0000519
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Reworks and Contractual Claims: The Salience of Contract Conditions

Abstract: Statistics show a high rate of contractual claims in construction projects, impacting the construction industry's progress negatively. 6 Rework is one of the main underlying factors that generate contractual claims. Rework and contractual claims follow a mutual routine. Despite 7 a large number of studies on the causes and impacts of rework on project performance, there has been limited research examining the relation-8 ship between claims and rework on the basis of contract documents. The paper first attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…As a result, the provided list is used to further investigate rework issues in the contracts by addressing rework causes in the contract terms and conditions. Addressing rework causes in the contract conditions results in fewer claims and disputes (Ndwandwa et al, 2017;Kim and Skibniewski, 2020;Asadi et al, 2022). Thus, the identified and classified rework causes in this study contributes to the body of knowledge in construction contracts.…”
Section: Background Of the Rework Classification Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…As a result, the provided list is used to further investigate rework issues in the contracts by addressing rework causes in the contract terms and conditions. Addressing rework causes in the contract conditions results in fewer claims and disputes (Ndwandwa et al, 2017;Kim and Skibniewski, 2020;Asadi et al, 2022). Thus, the identified and classified rework causes in this study contributes to the body of knowledge in construction contracts.…”
Section: Background Of the Rework Classification Methodsmentioning
confidence: 75%
“…Incorrect contract information is presumed to lead rework occurrence (Kakitahi et al, 2014). Searching the relationship between contract clauses and rework within various project stages would benefit future models of rework management by developing a framework that is capable to evaluate contracts in terms of identified rework causes (Mendis et al, 2015;Asadi et al, 2022). Identifying rework from a contract party's perspective will result in higher awareness of client and contractor by recognizing the root causes of rework at the time of contract preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the common causes of contractual claims and disputes is related to rework (Palaneeswaran, Love and Kumaraswamy, 2008;Wang, et al, 2019). The risk of claims and disputes is an inherent part of the rework in construction projects (Asadi, Rotimi and Wilkinson, 2022). Rework has been regarded as an issue affecting contractual claims in construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…According to ( Jelodar, Yiu and Wilkinson, 2016), rework, claims, and disputes arise from common sources. Even though most of the studies have identified the causes of rework and the causes of contractual claims separately, they have yet to examine or investigate the relationship between the rework, and the claims, and disputes (Asadi, Rotimi and Wilkinson, 2022). While many research studies have been conducted to understand the impacts of rework on project performance in the construction industry (Love and Edwards, 2004;Mahamid, 2016), very few have studied the effects of contractual claims originating from rework.…”
Section: Introductionmentioning
confidence: 99%